Understanding collective action and women's empowerment in potato farmer groups in Ntcheu and Dedza in Malawi - Mudege, Netsayi N.; Nyekanyeka, T.; Kapalasa, E.; Chevo, T.; Demo, P. (Elsevier, 2015)
This paper explores the potential for potato farmer groups to empower women in Malawi. It does this by examining how social and gender norms in communities, including the distribution of power, resources and responsibilities, may have an impact on the ability of farmer groups to empower female group participants.